Lab-based limits on the Carroll-Field-Jackiw Lorentz-violating electrodynamics - Gomes, Yuri; Cavalcanti Malta, Pedro (Physical review, 2016)
The CPT-odd and Lorentz-violating Carroll-Field-Jackiw modification of electrodynamics is discussed and we study its effects on the energy spectrum of hydrogen, as well as in the generation of a momentum-dependent electric dipole moment for charged leptons. We also briefly comment on the possibility of the detection of Lorentz violation in measurements of vacuum birefringence in resonant cavities. The bounds found are based on local laboratory experimental limits and are not competitive with the ones coming from astrophysical considerations.
Gesehen am 03.07.2020